The effect of chair massage on muscular discomfort in cardiac sonographers: a pilot study - Spittell Peter C; Oh Jae K; Persinger Colleen M; Nadolny Anita M; Wahner-Roedler Dietlind L; Engen Deborah J; Loehrer Laura L; Cha Stephen S; Bauer Brent A (BMC, 2010)
Abstract Background Cardiac sonographers frequently have work-related muscular discomfort. We aimed to assess the feasibility of having sonographers receive massages during working hours in an area adjacent to an echocardiography laboratory and to assess relief of discomfort with use of the massages with or without stretching exercises. Methods A group of 45 full-time sonographers was randomly assigned to receive weekly 30-minute massage sessions, massages plus stretching exercises to be performed twice a day, or no intervention. Outcome measures were scores of the QuickDASH instrument and its associated work module at baseline and at 10 weeks of intervention. Data were analyzed with standard descriptive statistics and the separation test for early-phase comparative trials. Results Forty-four participants completed the study: 15 in the control group, 14 in the massage group, and 15 in the massage plus stretches group. Some improvement was seen in work-related discomfort by the QuickDASH scores and work module scores in the 2 intervention groups. The separation test showed separation in favor of the 2 interventions. Conclusion On the basis of the results of this pilot study, larger trials are warranted to evaluate the effect of massages with or without stretching on work-related discomfort in cardiac sonographers. Trial Registration NCT00975026 ClinicalTrials.gov